Nerve morbidity following surgical removal of impacted mandibular third molar: A review of 178 cases - Rifqah Nordin; Nurkhairin Tajuddin; Norsamihah Anuar; Roszalina Ramli; Nalisha Mohamed Ramli (2024)
Volume 5 Issue 1 Page (14–18)